The development of Comic Stage Persona (CSP) in stand-up comedy: An interdisciplinary approach to an intersubjective performance phenomenon - NAESSENS, EDWARD DAVID (Trinity College Dublin. School of Creative Arts. Discipline of Drama, 2018)
Comedians learn how and who to be on stage. Writing and performing stand-up comedy entails complex social and professional challenges. Facing these challenges, stand-up comedians adapt personae. Via a critical analysis of research literature, humour theories, and first-person and third-person accounts of stand-up comedy and humour, the thesis identifies the need to bridge folk accounts to scientific method. The thesis appraises current approaches to humour and stand-up comedy, identifies conceptual difficulties and germane lines of discovery, and proposes remedies via NIGHTS (a Notionally Integrated General Humour Theory of Stand-up Comedy). The key claim of NIGHTS is that the performance of stand-up comedy begins as an intentioned process. The theoretical framework employed is a multi-disciplinary matrix under the umbrella of Daniel Dennett?s Heterophenomenological approach to the study of consciousness. Given that any meaningful investigation of CSP and humour entails studying first-person subjective reporting, Dennett?s Heterophenomenological approach provides a strategy that accommodates first-person subjective accounts within a third-person objective framework. The approach allows for engagement with first-person reports of stand-up comedy from comedians, coaches, spectators, and critics, without privileging such reports. In this way the thesis aims to bridge first-person accounts (folk theory) and scientific approaches to performance. The aim of the thesis is to engage with subjective accounts, unpack concepts (identifying compatibilities and conflicting concepts and definitions), and analyse stand-up comedy and the development of CSP in a way that is amenable to psychology and cognitive science.
APPROVED
Keywords: Humor Studies; Performance Studies; Cognitive Science Approach to Stand-up Comedy; Stand-up comedy; Persona formation; Stewart Lee; Comedy; Louis CK; Heterophenomenology; Performance of humour; Comic Stage Persona; Psychology of humour; Cognitive Science